2021
DOI: 10.3390/cancers13215506
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors, PROTACs and Molecular Glues as Diverse Therapeutic Modalities to Target Cyclin-Dependent Kinase

Abstract: The cyclin-dependent kinase (CDK) family of proteins play prominent roles in transcription, mRNA processing, and cell cycle regulation, making them attractive cancer targets. Palbociclib was the first FDA-approved CDK inhibitor that non-selectively targets the ATP binding sites of CDK4 and CDK6. In this review, we will briefly inventory CDK inhibitors that are either part of over 30 active clinical trials or recruiting patients. The lack of selectivity among CDKs and dose-limiting toxicities are major challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 149 publications
0
18
0
Order By: Relevance
“…To further test this hypothesis, we utilized PF-07104091 (CDK2i), a novel and selective small molecule inhibitor of CDK2 (Fassl et al, 2022; Jhaveri et al, 2021; Mezi et al, 2021; Rana et al, 2021). Cells were treated with 500nM CDK2i during the last hour of live-cell imaging before fixing at staining for DNA, EdU, NPAT, and either pNPAT T1270 or nascent histone RNA FISH (Figure 3G, see also Figure S3A-B).…”
Section: Resultsmentioning
confidence: 99%
“…To further test this hypothesis, we utilized PF-07104091 (CDK2i), a novel and selective small molecule inhibitor of CDK2 (Fassl et al, 2022; Jhaveri et al, 2021; Mezi et al, 2021; Rana et al, 2021). Cells were treated with 500nM CDK2i during the last hour of live-cell imaging before fixing at staining for DNA, EdU, NPAT, and either pNPAT T1270 or nascent histone RNA FISH (Figure 3G, see also Figure S3A-B).…”
Section: Resultsmentioning
confidence: 99%
“…[143][144][145][146][147] Many research groups were able to connect thalidomide analogs to specific protein inhibitors using a linker to produce new PROTACs such as the cyclin-dependent kinase (CDK) degraders 131 and 132 (Figure 12). [148][149][150][151][152][153] Studies indicated that MGs are more attractive when compared to PROTAGs due to their exceptional properties, such as molecular weight, which gives them more promising physiochemical and pharmacokinetic properties. In addition, MGs are not required to bind to the binding pocket of the targeted protein, hence it permits the molecule to be active despite its low affinity to the target protein.…”
Section: Protein Degradersmentioning
confidence: 99%
“…First of all, antibody–PROTAC conjugates can improve the pharmacokinetic properties of traditional small molecule PROTACs, increase their tissue selectivity, and avoid the side effects caused by protein degradation in normal cells 147 , 148 , 149 . Many of the in vivo assessments of degrader described in the previous literature have adopted a route of administration that may be difficult to convert to routine use in humans (for example, intraperitoneal administration) 150 , 151 .…”
Section: Antibody Protacsmentioning
confidence: 99%